Musik Sebagai Media Komunikasi Kesehatan Mental: Analisis Semiotika Lirik Lagu ‘Rehat’ Karya Kunto Aji - Setya Prihatining Tyas; Arfian Suryasuciramdhan; Alif Dava Mahesa; Annisa Putria Racmawati (STIKes Ibnu Sina Ajibarang, 2024)
This research investigates the influence of Kunto Aji's song 'Rehat' on promoting mental health awareness and improving well-being. Analysis was carried out on the lyrics, melody and inclusion of the Solfeggio frequency 396 Hz in the song to understand its therapeutic impact. The findings showed that the positive statements, soothing tunes, and calm atmosphere of the song produced a highly relatable healing impact on individuals. The song's widespread popularity and incorporation into various playlists and radio stations ensures its exposure to a wide audience, thus serving as a valuable instrument for increasing awareness of mental health and reducing the associated stigma. The involvement of psychologists in the song creation process emphasizes the importance of increasing awareness about mental health and the potential of music in facilitating this awareness. This study adds to the ongoing discourse about mental health awareness and the potential of music to improve mental well-being.